Implementasi Kolaborasi Orang Tua dan Guru Dalam Pelaksanaan Pembelajaran Daring pada PAUD - Moch. Surya Hakim Irwanto Hakim (IAI Al Khoziny Buduran Sidoarjo, 2020)
In current conditions it is highly recommended for all educational institutions to carry out online or online-based learning. Online implementation is carried out without meeting face to face with students. However, online implementation in PAUD really requires active participation from parents because of the condition of students who have not fully been able to access the media in online implementation. The purpose of this study is to describe online learning based on collaboration between parents and teachers in early childhood education. The method in this research is using descriptive qualitative research. The results of this study are expected that parents will be more motivated to take a proactive role in the learning process of children through online learning based on collaboration between parents and teachers.